DNA methylation as a marker for prenatal smoke exposure in adults. (31st May 2018) - Richmond, Rebecca C; Suderman, Matthew; Langdon, Ryan; Relton, Caroline L; Davey Smith, George
Abstract: Background: Prenatal smoke exposure is known to be robustly associated with DNA methylation among offspring in early life, but whether the association persists into adulthood is unclear. This study aimed to investigate the long-term effect of maternal smoke exposure on DNA methylation in 754 women (mean age 30 years); to replicate findings in the same women 18 years later and in a cohort of 230 men (mean age 53 years); and to assess the extent to which a methylation score could predict prenatal smoke exposure. Methods: We first carried out an epigenome-wide association analysis for prenatal smoke exposure and performed replication analyses for the top CpG sites in the other samples. We derived a DNA methylation score based on previously identified CpG sites and generated receiver operating characteristic (ROC) curves to assess the performance of these scores as predictors of prenatal smoke exposure. Results: We observed associations at 15 CpG sites in 11 gene regions: MYO1G, FRMD4A, CYP1A1, CNTNAP2, ARL4C, AHRR, TIFAB, MDM4, AX748264, DRD1, FTO (false discovery rate <5%). Most of these associations were specific to exposure during pregnancy, were present 18 years later and were replicated in a cohort of men. A DNA methylation score could predict prenatal smoke exposure (30 years previously) with an area under the curve of 0.72 (95% confidence interval 0.69, 0.76). Conclusions: The results of this study provide robust evidence that maternal smoking in pregnancy is associated with changes in DNA methylation that persist in the exposed offspring for many years after prenatal exposure.